Revisiting Collaboration Model for Process Innovation: Promoting Absorptive Capacity, Open Culture, and Trust - Manik, Hardo Firmana Given Grace; Lukito-Budi, Andy Susilo (Advances in Social Sciences Research Journal, 2020)
This conceptual paper presented a review of the company's model of collaboration with externalities in the context of process innovation from previous study of Un & Asakawa [51]. This paper extended the model from Un & Asakawa [51] by promoting three new moderating variables which were not taken into account earlier, i.e. absorptive capacity, open culture, and trust. The combination of all three variables together were proposed to have an impact to create a strong collaboration (strong ties). Conversely, if conditions of one or a combination of these three variables were not fulfilled (weak or insignificant) then the result of previous research results was likely to happen. Some suggestions about further work on this subject also were discussed.